Broadband mid-infrared emission around 2.9 μm in Dy3+ doped bismuth germanate glass. (December 2016) - Zhao, Guoying; Jin, Wentian; Fang, Yongzheng; Gong, Ting; Guo, Jinling; Dawai, Saya; Liao, Meisong; Hu, Lili
Graphical abstract: Highlights: A series of Dy 3+ doped bismuth germanate glass is synthesized. A flat and broad mid-infrared emission with a bandwidth of 374 nm was obtained in a 1.0mol% Dy2 O3 doped glass. The emission cross section at 2.9 μm reaches 7.78 × 10 −21  cm 2 . The origins of broadening 2.9 μm emission and energy transfer mechanism are discussed. Abstract: Bismuth germanate glasses doped with a series of different concentrations of trivalent dysprosium ions were synthesized using melt-quenching method. The complex glass network is characterized by Raman spectrum, to put in evidence a structure combining [BiO3 ] pyramidal units, [BiO6 ] octahedral units and [GeO4 ] tetrahedral units. The arrangement of these structural units attract the introduction of Dy 3+ ions thanks and endow the bismuth glass with the efficiently broadband mid-infrared emission. Upon the excitation source of an 808 nm laser diode, a flat and broad emission from 2.5 μm to 3.2 μm with a bandwidth of 374 nm was obtained in a 1.0mol% Dy2 O3 doped glass, which corresponds to 6 H13/2  →  6 H15/2 transition. The emission cross section around 2.9 μm is estimated to be 7.78 × 10 −21 cm 2 based on the fluorescence spectrum. Hence, the advantageous spectroscopic characteristics reveal that Dy 3+ doped bismuth gernamate glass is a potential cost effective host for the mid-infrared solid state lasers.